Grace and justice: the place of public utility (transitional justice and situations of necessity) - Ruiz Miguel, Alfonso (EUNOMÍA. Revista en Cultura de la Legalidad, 2018)
Abstract: This text, which is part of a wider study about grace, analyses the relationship between legal mercy and public utility. After distinguishing between reasons of clemency or compassion, justice and utility, the essay examines separately, firstly, the two basic criteria that are able to justify legal mercy: circumstances of restorative justice and situations of necessity; and, secondly, the proceedings and authorities suitable for that mercy (amnesties and either general or particular pardons).